Homoplasmic mitochondrial tRNAPro mutation causing exercise-induced muscle swelling and fatigue. (August 2020) - Auré, Karine; Fayet, Guillemette; Chicherin, Ivan; Rucheton, Benoit; Filaut, Sandrine; Heckel, Anne-Marie; Eichler, Julie; Caillon, Florence; Péréon, Yann; Entelis, Nina; Tarassov, Ivan; Lombès, Anne
Abstract : Objective: To demonstrate the causal role in disease of the MT-TP m.15992A>T mutation observed in patients from 5 independent families. Methods: Lactate measurement, muscle histology, and mitochondrial activities in patients; PCR-based analyses of the size, amount, and sequence of muscle mitochondrial DNA (mtDNA) and proportion of the mutation; respiration, mitochondrial activities, proteins, translation, transfer RNA (tRNA) levels, and base modification state in skin fibroblasts and cybrids; and reactive oxygen species production, proliferation in the absence of glucose, and plasma membrane potential in cybrids. Results: All patients presented with severe exercise intolerance and hyperlactatemia. They were associated with prominent exercise-induced muscle swelling, conspicuous in masseter muscles (2 families), and/or with congenital cataract (2 families). MRI confirmed exercise-induced muscle edema. Muscle disclosed severe combined respiratory defect. Muscle mtDNA had normal size and amount. Its sequence was almost identical in all patients, defining the haplotype as J1c10, and sharing 31 variants, only 1 of which, MT-TP m.15992A>T, was likely pathogenic. The mutation was homoplasmic in all tissues and family members. Fibroblasts and cybrids with homoplasmic mutation had defective respiration, low complex III activity, and decreased tRNA Pro amount. Their respiratory complexes amount and tRNA Pro aminoacylation appeared normal. Low proliferation in the absence of glucose demonstrated the relevance of the defects on cybrid biology while abnormal loss of cell volume when faced to plasma membrane depolarization provided a link to the muscle edema observed in patients. Conclusions: The homoplasmic MT-TP m.15992A>T mutation in the J1c10 haplotype causes exercise-induced muscle swelling and fatigue.